Visual design for a mobile pandemic map system for public health - Lwin, May Oo (2022)
Incidence and prevalence rates of dengue have increased over the years, and the disease is quickly becoming cause for concern within the public health community. Globally, 128 countries and slightly under four billion people are at risk of contracting dengue. In Sri Lanka, more than half of dengue cases originate in Colombo, which in previous years, used a manual pen-and-paper data management system, which meant that it was not possible to obtain or provide up-to-date information about the severity and spread of dengue. In 2015, two versions of a mobile application called Mo-Buzz Dengue were developed and launched in Colombo, Sri Lanka in order to overcome the challenges of the traditional management system by capitalizing on the rising affordability and ubiquity of mobile phone technology. To keep up with the dynamic nature of disease outbreaks, real-time data need to be visualized in a manner which facilitates discerning and comprehending these patterns. Hence, we used health maps in Mo-Buzz to effectively present this information. The first version of Mo-Buzz was for public health inspectors (PHIs), digitized data management as well as provided educational materials. The second version of Mo-Buzz was a source of information for the general public, a crowdsourcing platform to provide information relating to dengue transmission, and for health authorities to alert users to dengue-specific developments in their area. This paper illustrates the design considerations of the Mo-Buzz disease surveillance system for the general public. A draft scaled-down version of the PHI system was used to obtain feedback and make incremental design enhancements. Additionally, similar health maps were evaluated in terms of capability and usability. These findings were applied to identify future enhancements to the health map of Mo-Buzz Dengue.